Konsep Dakwah Damai Dalam Pemikiran Ulama Nusantara Dan Relevansinya Terhadap Kondisi Sosial Indonesia Masa Kini - Syauqi Liqo Irobbi; Puteri Mushlihatul Ummah; Aflahul Anam; Muhammad Rizki Syabani; Abdul Fadhil (Advances In Education Journal, 2025)
This study aims to explain the concept of peaceful da’wah in the thought of Nusantara scholars and assess its relevance to the current social conditions of Indonesian society. This research employs a literature-based method by examining classical and contemporary scholarly works, historical texts, da’wah manuscripts, and recent studies. The findings reveal that Nusantara scholars placed peaceful da’wah as a central approach through dialogue, exemplary conduct, and cultural adaptation. These principles remain relevant in addressing today’s social dynamics, particularly in strengthening tolerance, preventing conflict, and fostering harmonious social relations. The study concludes that the values of peaceful da’wah provide an essential foundation for responding to the complexities of Indonesia’s plural society